Mitochondrial genome characteristics and phylogenetic analysis of the medicinal and edible plant Mesona chinensis Benth - Tang, Danfeng; Huang, Suhua; Quan, Changqian; Huang, Yuan; Miao, Jianhua; Wei, Fan (Frontiers in Genetics, 2023)
Mesona chinensis Benth (MCB) (or Platostoma palustre or Platostoma chinense) is an important edible and medicinal plant in China. However, the mitochondrial genome (mitogenome, or mtDNA) of MCB has not been characterized or reported yet. In this study, we first sequenced and characterized the complete mitogenome of MCB. The MCB mitogenome was 494,599 bp in length and encoded 59 genes containing 37 protein-coding genes (PCGs), 19 tRNAs, and 3 rRNAs. Gene transfer analysis revealed that a total of 12 transfer segments with more than 93% identity (total length of 25,427 bp) were detected in the MCB mitogenome. Simple sequence repeats (SSR) analysis showed that 212 simple sequence repeats (SSR) were identified. Repeat sequence analysis revealed 305 repeat sequences (158 forward and 147 palindromic repeats) ranging from 30 bp to 48,383 bp and the 30–39 bp repeats were the majority type. Relative synonymous codon usage (RSCU) analysis uncovered that in total, 9,947 codons were encoding the protein-coding genes (PCGs). Serine (909, 9.1%) and leucine (879, 8.8%) were the two most abundant amino acids, while terminator (32, .3%) was the least abundant amino acid. Ka/Ks analysis indicated that almost all genes were subject to purification selection, except ccmB. Analysis of Lamiaceae mitogenomes constitution revealed that atpB and atpE were unique to the Rotheca serrata and Salvia miltiorrhiza mitogenomes. mttB gene loss was unique to the Boea hygrometrica mitogenome. The core fragments of the Lamiaceae mitogenomes harbored a higher GC content than the specific and variable fragments. In addition, phylogenetic analysis revealed that MCB was closely related to Salvia miltiorrhiza based on the mitogenomes. The current study provided valuable genomic resources for understanding and utilizing this important medicinal plant in the future.